ANALISIS YURIDIS HAK PATEN SEBAGAI OBJEK JAMINAN FIDUSIA DI INDONESIA DAN SEBAGAI OBJEK JAMINAN PERBANKAN DI SINGAPURA - Boy Ericson Siahaan (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2021)
Indonesia and Singapore have ratified TRIPs, which is an international agreement on IPR to be enforced in the national legal concepts of each country. Indonesia established its laws and regulations, namely Law no. 13 of 2016 concerning Patents and Singapore make it happen through the Singapore Patent Act Chapter 221 and in the Indonesian Patent Law Article 108 provides an opportunity for inventors to make the rights to the patent as an object of fiduciary guarantee. The Singapore government has realized the legal action as an object of guarantee that by approving the Masai Group company as the patent holder. This type of research is normative legal research, namely research conducted by analyzing written laws from library materials or secondary data and reference materials in the field of law or references in the field of law. The data used to answer the problems in this research is secondary data that comes from library research. The position of patent rights as objects must be in accordance with the objectives and functions of the law in the formation of laws and regulations both philosophically, sociologically and juridically. UU no. 42 of 1999 concerning Fiduciary Guarantees defines movable intangibles as objects of fiduciary security, while Law no. 13 of 2016 concerning Patents provides an explanation that the right to a patent is in the form of a patent certificate which is an intangible movable object and should be used as an object of fiduciary guarantee to provide legal certainty and the effectiveness of the law. Several inhibiting factors are the existence of implementing regulations which in this case have not yet been issued, the absence of an appraiser (appraiser) and the absence of a financing scheme. The Singapore government has realized the patent as a guarantee, this is because there is already a financing scheme and an appraiser service party to determine the value. The need for legal protection for patent holders so that more patents are created and more inventions occur, so that the country is more advanced.